Cosmology and convention. (February 2017) - Merritt, David
Abstract: I argue that some important elements of the current cosmological model are 'conventionalist' in the sense defined by Karl Popper. These elements include dark matter and dark energy; both are auxiliary hypotheses that were invoked in response to observations that falsified the standard model as it existed at the time. The use of conventionalist stratagems in response to unexpected observations implies that the field of cosmology is in a state of 'degenerating problemshift' in the language of Imre Lakatos. I show that the 'concordance' argument, often put forward by cosmologists in support of the current paradigm, is weaker than the convergence arguments that were made in the past in support of the atomic theory of matter or the quantization of energy. Highlights: Elements of the current cosmological model are conventionalist. These elements include dark matter and dark energy. The field is in a state of degenerating problemshift as defined by Lakatos.